A new platform for post-marketing surveillance and real-world evidence data collection for substance-based medical devices - Roberto Cioeta; Andrea Cossu; Emiliano Giovagnoni; Marta Rigoni; Paola Muti (Frontiers Media S.A., 2022)
The recent passage of European Union (EU) Regulation 2017/745 on medical devices (MDs) has improved the classification of MDs and revised their approval process and the post-marketing evaluation of their safety and effectiveness, promoting transparency and post-marketing oversight in Europe. This new regulation can better ensure patient safety and provide new opportunities for therapeutic innovation. In addition, the new regulations include and define MDs made of substances or of combinations of substances (substance-based MDs: SBMDs). The impressive growth of the MD, including SBMDs, that have been marketed over the recent years has likely been a relevant factor fueling this change. MD regulation requires a major effort from both industry and regulatory bodies to comply with its provisions. Manufacturers should produce sufficient clinical evidence that an MD, under normal conditions of use, provides adequate performance and that the foreseeable risks and frequency of adverse events (AEs) have an acceptable minimum rate, taking into account the benefits provided. We describe how we implemented the post-marketing surveillance (PMS) system of SBMDs to properly deal with post-market monitoring and confirmation of safety and performance, including AEs and the benefit-risk evaluation, as required by the 2017/745 Regulation. The two pillars of this novel system are: 1) passive vigilance, i.e., spontaneous reporting and 2) active post-marketing clinical follow-up (PMCF) activities, which systematically gather, record, and analyze real-world data (RWD) on performance, quality, function, use, tolerability, and safety of an MD, collected through a dedicated, structured web platform. Active PMCF is achieved through a process of generation, validation, and administration of digital questionnaires to all stakeholders, i.e., patients, physicians, both general practitioners and specialists, and pharmacists. The technology, potential use, advantages, and limitations of this large source of RWD are also discussed.